2013
DOI: 10.1097/brs.0b013e3182a42a68
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections in Spine Surgery

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(51 citation statements)
references
References 25 publications
7
41
2
1
Order By: Relevance
“…A study from the USA evaluating a total of 532 694 surgical procedures showed a prevalence of 0.7 infections per 100 procedures, 10-fold lower than that of LATAM in the current evaluation (Baker et al, 2016). Past estimates from the USA have indicated that as many as 3.2% of patients experienced an SSI after spinal surgery (Abdul-Jabbar et al, 2013). However, more recent reports have indicated a reduced incidence of SSI in spinal fusion surgeries (1.2%) (Baker et al, 2016), as well as orthopedic procedures like hip arthroplasty (1.5%) and knee arthroplasty (0.9%), likely due to institutional infection control measures and the use of vancomycin powder during surgery (Gaviola et al, 2016;Khan et al, 2014;Caroom et al, 2013).…”
Section: Discussionmentioning
confidence: 52%
“…A study from the USA evaluating a total of 532 694 surgical procedures showed a prevalence of 0.7 infections per 100 procedures, 10-fold lower than that of LATAM in the current evaluation (Baker et al, 2016). Past estimates from the USA have indicated that as many as 3.2% of patients experienced an SSI after spinal surgery (Abdul-Jabbar et al, 2013). However, more recent reports have indicated a reduced incidence of SSI in spinal fusion surgeries (1.2%) (Baker et al, 2016), as well as orthopedic procedures like hip arthroplasty (1.5%) and knee arthroplasty (0.9%), likely due to institutional infection control measures and the use of vancomycin powder during surgery (Gaviola et al, 2016;Khan et al, 2014;Caroom et al, 2013).…”
Section: Discussionmentioning
confidence: 52%
“…Early SSIs, potentially predominant reason for early reoperations following spinal surgery, occur at an average time of 3 weeks after the index procedure. [6,7] We believe that early SSIs should be included in the causes of ''early reoperations,'' and we therefore defined 30 days as the period of interest in this study. On the other hand, in the United States, 30-day readmission is considered one of the problems of the health care system [8][9][10], and hospitals with a high 30-day unplanned readmission rate may be financially penalized in the near future [11].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 4 , 5 An increase in the proportion of SSI following arthroplasty and spine fusion caused by GNB has been recently reported nationwide. 4 , 6 8 Also, an increased resistance of GNB to cefazolin has been observed. 6 8 Accordingly, current clinical practice guidelines for antimicrobial prophylaxis in surgery recommend using active surveillance and local resistance patterns when selecting agents for perioperative prophylaxis.…”
Section: Introductionmentioning
confidence: 96%
“… 4 , 6 8 Also, an increased resistance of GNB to cefazolin has been observed. 6 8 Accordingly, current clinical practice guidelines for antimicrobial prophylaxis in surgery recommend using active surveillance and local resistance patterns when selecting agents for perioperative prophylaxis. 4 …”
Section: Introductionmentioning
confidence: 96%